Alliance Governance Mechanisms in the Face of Disruption - Keller, Arne; Lumineau, Fabrice; Mellewigt, Thomas; Ariño, Africa (Organization Science, 2021)
Existing academic literature has discussed contracts and relational governance as the key mechanisms that help alliance partners address problems of cooperation and coordination. However, when an alliance undergoes disruption, the nature and extent of such problems may change and therefore the value of these mechanisms may change. This study advances a dynamic perspective on alliance governance by examining the impact of disruption and subsequent adjustment on the value of alliance governance mechanisms. To this end, we longitudinally studied a revelatory case of a research and development alliance in the veterinary drug industry that experienced disruption triggered by an internal restructuring at one of the partner companies. We approached the evidence with a fine-grained typology that builds on two dimensions that underlie governance mechanisms: the means to enforce their ruling principles (contractual versus relational) and the level of codification of these principles (formal versus informal). Based on our findings, we (1) show the significance of this revised typology, which suggests that contractual governance is not necessarily formal and relational governance is not necessarily informal; (2) provide a more systematic discussion of the tradeoffs that the various mechanisms entail and how these are altered through disruption and adjustment dynamics; and (3) analyze how the interplay between different types of governance mechanisms evolves following disruption and adjustment. Overall, our study brings the concept of disruption to the dynamic perspective of alliance governance and highlights the contingent value of alliance governance mechanisms.